What We Talk About When We Talk About Pride: A Constructivist Grounded Theory Study - Tompkins, Trudy Marie, author; Steger, Michael F., advisor; Conner, Bradley T., committee member; Gardner, Danielle, committee member; Aoki, Eric, committee member (Colorado State University. Libraries, 2026)
Current research regarding LGBTQ+ Pride emphasizes Pride in one’s identity or identification with the LGBTQ+ community (Shiota et al., 2006; Testa et al., 2015; Hidalgo et al., 2019; Perrin et al., 2020; Rendina et al., 2019). This understanding of Pride does not acknowledge the historical significance of how Pride became a construct within LGBTQ+ research, with its creation paralleling the events of the Stonewall Riots; an event that triggered a large increase in LGBTQ+ advocacy, acceptance, and research (Davidson, 2021; Hood, 1998; Thorstad, 1995; Horne et al., 2010). Discourse within the LGBTQ+ community draws attention to the multifaceted nature of the emotional experience of Pride (Reddit thread: “What does Pride mean to you?” r/lgbt). Therefore, how LGBTQ+ Pride is defined in research potentially minimizes the construct, contributing to a conceptual misalignment between researchers’ definitions of Pride and the LGBTQ+ community’s experience of Pride. The purpose of the present study was to gain a wholistic understanding of the experience of Pride by LGBTQ+ individuals as both the social construction of historical events of Pride, and as the definition and emotional experience of LGBTQ+ Pride. To address this conceptual misalignment, this study used constructivist grounded theory to evaluate how Pride is conceptualized within the LGBTQ+ community. Analysis of 7 semi structured interviews resulted in a theory of how Pride is created, and experienced, within the LGBTQ+ community.
Keywords: LGBTQIA; Qualitative; Pride; Grounded Theory